Pelatihan Penerapan Sistem Data Statistik Penelitian Mahasiswa Tingkat Akhir Agrobisnis Perikanan Fakultas Perikanan dan Ilmu Kelautan UHO - Nurhuda Annaastasia; Akhmad Mansyur; Nurdiana A; Azwar Siddiq (Universitas Mataram, 2022)
One of the difficulties that final year students experience is processing, analyzing, presenting and interpreting data. This is a problem in accelerating the completion of student studies. This service is a mentoring activity for final year students both in processing research data and in designing analytical frameworks and testing the validity of research instruments. This service is carried out as an effort to accelerate the completion of student studies who are still constrained by the ability and skills of data processing, data presentation, and data interpretation. With this service activity, students are expected to be able to overcome each of these obstacles. The target of this service is the students of the Department of Fisheries Agribusiness, Faculty of Fisheries and Marine Sciences UHO who have completed the proposal exam and conducted research using quantitative methods, totaling 50 people. This service activity was carried out by presenting material using power point media and analyzing data using SPSS software version 22 and Microsoft Office Excel. The performance assessment of the implementation of this service is carried out based on the pre-test and post-test approaches. As a result, in the pre test, about 56% of students did not understand the application of statistical data systems in completing their final project and the results of the pro test increased by about 21% after going through the process of exposure and material practice. In the training using the Statistical Product and Service Solutions (SPSS) analysis tool. version 22 and Microsoft Office Excel. In order to be more optimal in improving understanding of the application of statistical data systems, it is better to provide training not only once but can be scheduled every year so that it can help students, especially in accelerating the completion of their final assignments.